Regulatory focus and consumption of counterfeit luxury goods: Roles of functional theories of attitudes and perceived similarity - Wang, Li; Jin, Manhui; Yang, Zhiyong (Journal of business research, 2020)
Four studies show that promotion (vs. prevention) focus leads to greater counterfeit consumption, and that social functions of attitudes and perceived similarity form a chain mediation underlying these effects. Study 1 links chronic regulatory focus to counterfeit consumption behavior in both China and South Korea. Study 2 replicates Study 1′s findings using primed regulatory focus and a behavioral measure of counterfeit preference. Study 3 tests the effect of regulatory focus on counterfeit consumption in a different context and demonstrates the mediating roles of social functions of attitudes and perceived similarity. Study 4 examines the boundary condition of social functions of attitudes: When social-adjustive function is made salient (compared to a control condition), prevention-focused consumers’ counterfeit consumption is elevated, whereas promotion-focused consumers’ counterfeit consumption is unaffected. However, when value-expressive function is made salient (compared to a control condition), promotion-focused consumers’ counterfeit consumption is reduced, whereas prevention-focused consumers’ counterfeit consumption is unaffected.